2021
DOI: 10.1186/s13046-021-02008-3
|View full text |Cite
|
Sign up to set email alerts
|

USP1-dependent RPS16 protein stability drives growth and metastasis of human hepatocellular carcinoma cells

Abstract: Background Hepatocellular carcinoma (HCC) remains a medical challenge due to its high proliferation and metastasis. Although deubiquitinating enzymes (DUBs) play a key role in regulating protein degradation, their pathological roles in HCC have not been fully elucidated. Methods By using biomass spectrometry, co-immunoprecipitation, western blotting and immunofluorescence assays, we identify ribosomal protein S16 (RPS16) as a key substrate of ubiqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…Studies have shown that in the antiviral response signaling pathway of type I interferon, the deubiquitinase USP1 interacts with TBK1 to deubiquitinate TBK1, enhance the expression of downstream type I interferon, and inhibits viral replication ( Yu et al., 2017 ). A previous study found an interaction between RPS16 and USP1 in hepatoma cells ( Liao et al., 2021b ). Also, our result showed that knockdown of RPS16 in the cell obviously increased the phosphorylation of TBK1 ( Figure 7G ).…”
Section: Resultsmentioning
confidence: 85%
“…Studies have shown that in the antiviral response signaling pathway of type I interferon, the deubiquitinase USP1 interacts with TBK1 to deubiquitinate TBK1, enhance the expression of downstream type I interferon, and inhibits viral replication ( Yu et al., 2017 ). A previous study found an interaction between RPS16 and USP1 in hepatoma cells ( Liao et al., 2021b ). Also, our result showed that knockdown of RPS16 in the cell obviously increased the phosphorylation of TBK1 ( Figure 7G ).…”
Section: Resultsmentioning
confidence: 85%
“…Recently, increasing DUBs were identified as tumor promoters via deubiquitinating and stabilizing certain oncoproteins in cancers, and were proposed as novel therapeutic targets. In this study, we showed that ARV-771 can downregulate multiple DUBs in HCC, including USP1, USP8, USP10, USP13, and USP18, which have been implicated in the tumorigenesis and progression by regulating certain substrates ( Cai et al, 2017 ; Gao et al, 2020 ; Zhu et al, 2020 ; Liao et al, 2021b ; Zhu et al, 2021 ). Therefore, we hypothesized that the reduction of USP1, USP8, USP10, USP13, and USP18 may all involve in the ARV-771-induced growth inhibition in HCC.…”
Section: Disccussionmentioning
confidence: 80%
“…Recently, the roles of DUBs have been highlighted in the progression of HCC. For example, the ubiquitin-specific peptidase 1 (USP1) may promote proliferation and migration of HCC via controlling the protein stability of ribosomal protein S16 (RPS16) ( Liao et al, 2021b ). Additionally, the USP14 can also facilitate cell proliferation and migration by maintaining HIF1-α stability in HCC ( Lv et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the high expression of USP1 and RPS16 in liver tissue is a prognostic factor for poor survival of HCC patients. 31 …”
Section: Discussionmentioning
confidence: 99%